Wireline Log Responses, Mudweight, Clay Mineralogy, and Implied Overpressure Condition: Insights from Aru Field, North Sumatra Basin - Mohammad Syaiful; Lambok M. Hutasoit; Agus M. Ramdhan; Agus Haris Widayat (Geological Agency, 2020)
DOI:10.17014/ijog.7.2.105-119This paper comprehensively discusses overpressuring in the North Sumatra Basin by using wireline log, drilling events and parameters, and clay mineralogical data. It shows an interesting phenomenon related to overpressuring in this basin, i.e. strong log reversals indicating high overpressure, yet the mudweight used during drilling was relatively low, indicating low overpressure with no significant drilling events noted in the final well report.The result of the study shows that wireline log is the best parameter to imply overpressure magnitude. Regarding low mudweight in the strong log reversal zone, it would be elucidated that the drilling in that zone was in underbalance condition with respect to shale pressure, but not to sandstone pressure. The sandstone pressure is interpreted to be lower than shale pressure due to lateral drainage process. By applying the Eaton’s method, the estimated maximum overpressure magnitude in the Baong Formation is in the range of 1,594 - 3,185 psi. or equivalent to the mudweight of 1.61 - 192 g/cm3. The analysis of wireline log in combination with clay mineralogical data shows that there are two compaction lines in the studied area, i.e. smectitic and illitic compaction lines. The cross-plot of density and sonic logs in shale section suggest that the cause of overpressure was loading mechanism. The scanning electron microscope (SEM) image confirms that in overpressure zone, grain to grain contact is still able to be observed fairly well, inferring that loading mechanism is really the cause of overpressure in the studied area.